Integrasi Agama, Masyarakat dan Budaya: Kajian tentang Tradisi Haul dan Ziarah dalam Masyarakat Palembang - Rajasyah, M Adhim (Jurnal Riset Agama, 2023)
This research aims to examine the pilgrimage and haul carried out as a tradition in Palembang City, which is the area with the most graves of aulia solihin and waliyullah. This research uses a descriptive qualitative method to describe the history and series of haul and kubro pilgrimage implementation as a tradition in Palembang city, using a literature approach and direct observation in the field where activities occur directly. The results and discussion of this research show that the preservation of Palembang culture has a positive impact. The purpose of this research is to find out how the presence of kubro pilgrimage carried out by the Arab community in Palembang city and to find out how the integration of religion, society and culture in the tradition of kubro pilgrimage in the Palembang city community.